Using Word-Dependent Transition Models in HMM based Word Alignment for Statistical Machine Translation - He, Xiaodong (in ACL workshop on SMT (WMT), 2007)
In this paper, we present a Bayesian Learning based method to train word dependent transition models for HMM based word alignment. We present word alignment results on the Canadian Hansards corpus as compared to the conventional HMM and IBM model 4. We show that this method gives consistent and significant alignment error rate (AER) reduction. We also conducted machine translation (MT) experiments on the Europarl corpus. MT results show that word alignment based on this method can be used in a phrase-based machine translation system to yield up to 1% absolute improvement in BLEU score, compared to a conventional HMM, and 0.8% compared to a IBM model 4 based word alignment.